Emovere: como podemos usar as emoções e a computação afetiva no design de um jogo - Batista, Andreia Filipa dos Santos (2020)
This master by project seeks to inquire possible links between emotions, affective computing and digital games. From the main research question, “How can we use emotions and affective computing in a game design?”, It was necessary to do a study about emotions, investigating what their role in human life is. Following this preliminary analysis of emotions, a link has been established with affective computing, in particular, one of its ramifications, affective games, which adds games to the equation. In the following, it was questioned how to measure existing emotions and the best methods to measure them. Finally, starting from some of the secondary research questions, as follows, “what differentiates affective games from others?”; “what is the best form of interaction with affective games?”; "what makes players want to play or continue playing affective games?"; a digital typing game named Emovere was produced. The creation and development of the project Emovere had as its starting point a crossover of interests, aroused by the determination to understand how we can take advantage of emotions, and what strategies to use to intensify and highlight their role, both when developing a digital game and during the act of playing the same game. In an initial stage research, which covered not only the sphere of emotions but also games, through Game Design, it was possible to find a link between them, relevant to theoretical development: the area of affective computing. Based on the information gathered, it aimed to answer the main research question, thus creating the necessary theoretical foundation for the construction of a project proposal. Through an exploratory methodology based on arts and design research the work was structured in four chapters that are briefly presented in the introduction. An original interactive script was created which can be consulted in the appendices of the document. Finally, the culmination of the information gathered over the first three chapters results in a proposal for the creation and development of an affective digital typing game presented in chapter four which aims to mirror the importance of emotions in game design and development, making use of the methodologies used by affective computing in the collection and measurement of affective information. This case study aims to get the best out of the fundamentals obtained so far, in order to provide the player with not only the best possible emotional experience but also a self-reflective experience about the emotions and feelings that come from certain stimuli, and the unique ability of games to provoke them.